Keadilan, Penghukuman, Pengharapan: Kontribusi Teologis Kitab Mikha bagi Umat - Lili Lili; Maria Evvy Yanti (JURNAL TEOLOGI GRACIA DEO, 2021)
A life that upholds obedience to God will create individuals who have integrity in moral practice according to His will. But this is faced with a situation of the times that shows the disobedience committed by the group that become the enforcer of the truth. The hope of the people as expressed through the truth and justice of the leaders accompanied by condemnation for their perversion of behavior. The situation of life that occurred was the same as that experienced by the Israelites at the time of the preaching of the book of Micah. This study aims to analyze the theological message of the book of Micah which is loaded with the teachings of behavior to exercise obedience and diligence on God's will in the midst of the punishment experienced by the people. In addition, the narrative written in the book of Micah is very interesting because in the midst of god's condemnation bestows salvation for the people. The method used in this study is qualitative by applying descriptive methods through historical analysis of the social situation of the text. This research shows that people's practices of life are centered on obedience to teach God's truths that occur in the lives of people. AbstrakKehidupan yang menjunjung tinggi ketaatan kepada Allah akan menciptakan individu yang memiliki integritas dalam praktik moral sesuai dengan kehendak-Nya. Tetapi hal ini dihadapkan pada situasi zaman yang menunjukkan ketidaktaatan yang dilakukan oleh kelompok yang diamanahkan menjadi penegak kebenaran. Harapan umat dinyatakan melalui tindakan kebenaran dan keadilan dari para pemimpin disertai dengan penghukuman atas penyimpangan perilaku mereka. Situasi kehidupan yang terjadi sama seperti yang dialami oleh orang Israel pada saat pemberitaan kitab Mikha. Penelitian ini bertujuan untuk menganalisis pesan teologis kitab Mikha yang sarat dengan ajaran perilaku untuk menjalankan ketaatan dan ketekunan pada kehendak Tuhan di tengah hukuman yang dialami oleh umat. Selain itu, narasi yang ditulis dalam kitab Mikha sangat menarik karena di tengah kecaman Allah menganugerahkan keselamatan bagi umat. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan menerapkan metode deskriptif melalui analisis sejarah situasi sosial teks. Penelitian ini menunjukkan bahwa praktik kehidupan masyarakat berpusat pada kepatuhan untuk mengajarkan kebenaran Tuhan yang terjadi dalam kehidupan umat.